Sleep quality of patients being followed up at the geriatric outpatient clinic (Research, Society and Development, 2023)
With the population aging process in Brazil, problems related to the health of aged have been gaining importance in the medical office. One of the main complaints of this patient are those related to sleep, as there are physiological changes in the sleep-wake cycle in senescence, which may or may not be accompanied by sleep disorders. This study aims to evaluate the sleep quality of patients being monitored at the Elderly Health Clinic at the Center for Medical Specialties of CESUPA (CEMEC). A quantitative approach research was carried out on an outpatient basis within a private higher education institution in the city of Belém-PA. For data collection, the Pittsburgh Sleep Quality Index questionnaire was used and 112 patients were included in the research, aged between 60 and 104 years, the majority (75.9%) were female. Regarding the quality of sleep assessed by the PSQI, 15.2% of the patients had good quality (95%CI 9.3 – 23.5), 49.1% had poor quality (95%CI 39.6 – 58.7) and 35.7% sleep disorder (95%CI 27.0 – 45.4). Based on the above, there is a need for health professionals to know how to address sleep-related complaints in elderly patients, since poor sleep quality has a negative impact on their expectation and quality of life.